2(y-8)=y+6

Simple and best practice solution for 2(y-8)=y+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(y-8)=y+6 equation:


Simplifying
2(y + -8) = y + 6

Reorder the terms:
2(-8 + y) = y + 6
(-8 * 2 + y * 2) = y + 6
(-16 + 2y) = y + 6

Reorder the terms:
-16 + 2y = 6 + y

Solving
-16 + 2y = 6 + y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
-16 + 2y + -1y = 6 + y + -1y

Combine like terms: 2y + -1y = 1y
-16 + 1y = 6 + y + -1y

Combine like terms: y + -1y = 0
-16 + 1y = 6 + 0
-16 + 1y = 6

Add '16' to each side of the equation.
-16 + 16 + 1y = 6 + 16

Combine like terms: -16 + 16 = 0
0 + 1y = 6 + 16
1y = 6 + 16

Combine like terms: 6 + 16 = 22
1y = 22

Divide each side by '1'.
y = 22

Simplifying
y = 22

See similar equations:

| 2.5=ln(7/x) | | 7=ln(2.5/x) | | 18y^2-37y-20=0 | | 2+.08x=.2x+8 | | Z2/6-7z/2-12=0 | | 6x^2+43x-15=0 | | 6/7z=3 | | 25a^2+25ac-14c^2=0 | | -6.1c=-24.4 | | 3(a+m)+2(b+n)-3a-2b=0 | | 3x-1=6T+2 | | 23x+98=63 | | p-40=24.76 | | h^2+11h+4=0 | | Log(67)=log(21x) | | 3(a+m)+2(b+n)=3a+2b | | -x+12=6 | | -z+2=13 | | 67=21x | | 4n-6-5n=8-n+7 | | 1/2×-2=2-5/3× | | 21xy/20x | | .16x+.6(x-4)=.01(3x-3) | | t-5+6t=3(3t-3) | | -6(4x-4)+8=-24x+32 | | 5p+3=3(3p-5) | | 2n+59=-4-5n | | -16+5n=-7-6+8n | | -3y/-3=25/-3 | | 7=1/2(-m-5) | | (1-4p)/50.2 | | 24=15-(4z-3) |

Equations solver categories